2019
DOI: 10.4193/rhin19.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of triamcinolone versus normal saline soaked polyvinyl alcohol pack following bilateral endoscopic sinus surgery

Abstract: Background: Steroids have been proven to be beneficial in improving post-operative outcomes following sinus surgery. The ideal mode of delivery is to increase local concentration in the sinuses with minimal systemic side effects. In this study, we used triamcinolone soaked polyvinyl alcohol packs immediately following sinus surgery, and assessed the effects on post-operative outcomes. Methodology: This was a prospective, interventional, and comparative study. Following endoscopic sinus surgery, a polyvinyl alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Gyawali et al 2258 reported an RCT of 58 patients comparing triamcinolone‐impregnated polyvinyl alcohol packs placed as a spacer, with saline‐impregnated packs, which were removed on day 2. The side for the triamcinolone pack was chosen randomly and the opposite side served as the saline control; observers were blinded to side.…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Gyawali et al 2258 reported an RCT of 58 patients comparing triamcinolone‐impregnated polyvinyl alcohol packs placed as a spacer, with saline‐impregnated packs, which were removed on day 2. The side for the triamcinolone pack was chosen randomly and the opposite side served as the saline control; observers were blinded to side.…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Although most of the studies showed a trend favoring steroid use, 10,13,[16][17][18][19][20][21][22][23][27][28][29][30] some studies still demonstrated a favorable trend toward no steroids. This phenomenon might be due to nasal irrigation or postoperative oral steroids in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the outcome of Lund–Kennedy scores, most of the studies showed a decrease in endoscopic score to near perfect in the steroid group 26 after 2 weeks postoperatively. Although most of the studies showed a trend favoring steroid use, 10,13,16–23,27–30 some studies still demonstrated a favorable trend toward no steroids. This phenomenon might be due to nasal irrigation or postoperative oral steroids in both groups 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the pricing is higher than that of nasal packing which could well be a reason not to implement this strategy (178) . Infiltrating nasal polyvinyl alcohol packs with triamcinolone showed additional benefit in the postoperative recovery (179) .…”
Section: Surgery and Post-operative Care In Crsmentioning
confidence: 98%